Analysis of Determinants of Hypertension in Adult Population: Case-Control Approach - sri handayani; Edison Edison; Eliza Trisnadewi (Jurnal Kesehatan Medika Saintika, 2025)
Hypertension means the blood pressure in the blood vessels is very high with an increase in systolic blood ≥ 90mmHg. Hypertension is a non-communicable disease that is a global health problem. Hypertension data. The aim of the research is to determine the factors that influence the incidence of hypertension. The type of research is analytical observational with a case control approach. This research was conducted at the Air Haji health center in 2024. The population in this study was 368 hypertension sufferers with a sample of 146 cases and 146 controls. Sampling used the Accidental Sample technique. Data were analyzed univariately and bivariately using the Chi-square test. The results showed the frequency of hypertension in cases (50.0%), controls (50.0%), obesity (58.9%), stress (56.2%), and smoking (62.7%). There is a relationship between obesity (p=0.012 with OR=1.874), stress (p=0.003 with OR=4.81) with the incidence of hypertension at the Air Haji Health Center in 2024. There is no relationship between smoking (p=0.468 with OR=1.228) with the incidence hypertension. It was concluded that there is a relationship between obesity and stress and the incidence of hypertension. There is no relationship between smoking and the incidence of hypertension. It is hoped that the community health center can increase the development of health promotion programs and can provide education about hypertension, the factors that cause it. and a healthy and regular lifestyle to avoid hypertension.